(untitled) (Sains Humanika, 2022)
Vocabulary is an essential part of language learning. Vocabulary can be acquired incidentally or intentionally. In Malaysian classroom, vocabulary is mainly learnt through rote learning, where learners are drilled to remember the words through reusing the words in different tasks. Most of the time, vocabulary learning is a conscious process. On the contrary, incidental vocabulary acquisition is uncommon especially among young English as Second Language (ESL) learners. Incidental vocabulary acquisition is a process where acquisition can occur through reading and narrow reading is a useful strategy to consolidate the learning of new vocabulary. The main objective of this study is to investigate the effectiveness of narrow reading in improving incidental vocabulary acquisition among young learners in ESL context. The study involved thirty primary school pupils from a sub-urban school in Johor Bahru. Three instruments were used in this study, (i) pre- and post-tests, (ii) questionnaire, and (iii) semi-structured interview. The findings from the pre-test and post-test showed an increase in the mean of the scores. From the questionnaire, more than fifty percent of the pupils agreed that reading from thematically related texts helped them to enjoy reading and enabled them to understand the vocabulary. Findings from the semi-structured interview generated two themes, (i) self-directed learning, and (ii) motivation to read. Hence, narrow reading in the ESL classroom helps in acquiring incidental vocabulary among the pupils. It is recommended that narrow reading can be introduced in the ESL Malaysian classroom to encourage incidental vocabulary acquisition especially among young learners.